2019
DOI: 10.5539/elt.v12n3p77
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Teacher-Led and Online Text-to-Speech Dictation for Students’ Vocabulary Performance

Abstract: Researchers have long supported the use of dictation as a test for language learners (Fountain & Nation, 2000), and dictation has been used as a test for learners of English as a foreign language (EFL). With the advantages of productive learning and reinforcing short-term memory, dictation is a commonly used technique to develop language skills, and it can be considered to be an assessment of foreign language learning (Kazazoğlu, 2013). However, the previous research has not fully explored how technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In the context of the learning process, Parr (2012) pointed out that text-to-speech runs the risk of stigmatizing students who are perceived to be different, who are privileged in the sense that they have a computer, or who are accused of cheating. Chiang (2019) found that students' perception is different with the improvement of their performance on learning. They seemed to strongly agree with the statement "The teacher is the role model for pronunciation in the classroom" because TTS technology is sometimes still very mechanical and does not sound emotional.…”
Section: Text-to-speech Disadvantages In Language Learningmentioning
confidence: 98%
“…In the context of the learning process, Parr (2012) pointed out that text-to-speech runs the risk of stigmatizing students who are perceived to be different, who are privileged in the sense that they have a computer, or who are accused of cheating. Chiang (2019) found that students' perception is different with the improvement of their performance on learning. They seemed to strongly agree with the statement "The teacher is the role model for pronunciation in the classroom" because TTS technology is sometimes still very mechanical and does not sound emotional.…”
Section: Text-to-speech Disadvantages In Language Learningmentioning
confidence: 98%
“…There was a correlation between TTS dictation and teacher-led dictation scores, i.e., students who performed better with teacherled dictation also obtained higher scores with TTS dictation (Chiang, 2019). In addition, students with learning disabilities who struggle with reading and comprehension benefit from TTS software when used as a supplement to explicit teacher instruction.…”
Section: Introductionmentioning
confidence: 93%
“…There are numerous platforms that can be used to conduct the dictation in an online environment, but detailed analyses of the same reveal a number of shortcomings that make them impractical for further use in a classroom situation. Most of these platforms are based on the idea of converting text to speech, which is a technologically advanced alternative for reading text out loud in situations when the teacher is absent [5,6,7]; however, it is rather inconvenient to be used as a platform for conducting a writing activity such as dictation since the reading is continuous and has no characteristics of the traditional dictation reading (the example of such platforms are: Natural readers 1 and From text to speech 2 ). On the other hand, there are platforms such as Speechling 3 , DailyDictation 4 , and Listen and Write 5 that allow users to control the speed of dictation, insert the text for dictation and see corrections immediately after the dictation is completed; however, the limitations of these platforms are reflected in the inability of the teacher to see students' results -since these platforms' primary function is to support independent language learning outside of the classroom situation.…”
Section: Related Workmentioning
confidence: 99%